PERAN PINJAMAN PERBANKAN TERHADAP PERTUMBUHAN EKONOMI DI PROVINSI BALI - I GUSTI AYU MADE AGUNG MAS ANDRIANI PRATIWI; I WAYAN SUARBAWA (GANEC SWARA, 2024)
Sustainable economic growth reflects increased economic activity, which ultimately contributes to improving people's welfare. Economic growth in Bali Province has experienced fluctuations over the past five years, one of the causes is the covid-19 pandemic which has shaken the regional economy. One of the instruments needed to support post-pandemic economic recovery is the use of financial instruments, namely bank lending. This research is focused on discussing the description of bank loans associated with economic growth in Bali Province. The purpose of this study is to determine the effect of working capital loans, investment loans, and consumption loans partially and simultaneously on economic growth in Bali Province. The approach used in this research is a quantitative approach. This study uses secondary data obtained from BPS Bali Province. The data used in this study are time series data for each regency / city in Bali Province in 2019-2023. This research uses data processing tools, namely Microsoft Excel and SPSS. The results showed that: (1) working capital loans and consumption loans have a partially positive effect on economic growth, while investment loans have a partially negative effect on economic growth in Bali Province; and (2) capital loans, investment loans, and consumption loans simultaneously affect economic growth in Bali Province.